Analisis Dan Perancangan User Interface Sistem Pembayaran SPP Pada STMIK Primakara Berbasis Web - Ni Putu Anik Mentayani; I Putu Satwika (Primakara University, 2021)
STMIK Primakara is a College of Informatics and Computer Management that provides education in the IT field at the S1 level, where the main cycle of income is in the form of DPP (Education Development Fund) and SPP (Education Development Donations) payments. Recording of SPP payments and management of financial data at STMIK Primakara have started using the system but the system is not yet integrated with each other, where the finance party still has to edit income in the form of Microsoft Excel from the bank and then filter what data is needed then upload it to the financial system. Seeing these problems, the authors conducted an analysis and provided a solution for STMIK Primakara in the form of a web-based SPP payment system at STMIK Primakara using the System Development Life Cycle (SDLC) method. The results of this study are a web-based tuition payment user interface design at STMIK Primakara to serve as a reference in making a tuition payment system later. With this system, it can make it easier for students and finance to process tuition payment transactions.